Using Blockchain to Improve Decision Making That Benefits the Public Good - Cerf, Moran; Matz, Sandra; Berg, Aviram (Frontiers in Blockchain, 2020)
Human decision making is often prone to biases and irrationality. Group decisions add dynamic interactions that further complicate the choice process and frequently result in outcomes that are suboptimal for both the individual and the collective. We show that an implementation of a Blockchain protocol improves individuals’ decision strategies and increases the alignment between desires and outcomes. The Blockchain protocol affords (1) a distributed decision, (2) the ability to iterate repeatedly over a choice, (3) the use of feedback and corrective inputs, and (4) the quantification of intrinsic choice attributes (i.e., greed, desire for fairness, etc.). We test our protocol’s performance in the context of the Public Goods Game. The game, a generalized version of the Prisoner’s Dilemma, allows players to maximize their own gain or act in ways that benefit the collective. Empirical evidence shows that participants’ cooperation in the game typically decreases once a single player favors their own interest at the expense of others’. In our Blockchain implementation, “smart contracts” are used to safeguard individuals against losses and, consequently, encourage contributions to the public good. Across different tested simulations, the Blockchain protocol increases both the overall trust among the participants and their profits. Agents decision strategies remain flexible while they act as each other’s source of accountability (which can be seen as formalized distributed “Ulysses contract”). To highlight the contribution of our protocol to society at large we incorporated an entity that represents the public good. This benevolent independent beneficiary of the contributions of all participants (e.g. a charity organization or a tax system) maximized its payoffs when the Blockchain protocol was implemented. We provide a formalized implementation of the Blockchain protocol and discuss potential applications that could benefit society by more accurately capturing individuals’ preferences. For example, the protocol could help maximize profits in groups, facilitate democratic election that better reflect the public opinion, or enable group decision in circumstances where a balance between anonymity, diverse opinions, personal preferences and loss-aversion play a role.